中国城市基础设施投资触资机制分析 = Analysis of investment and financing mechanism for the urban infrastructure construction in China - 张雷 Zhang, Lei (2008)
Urban infrastructures are the basis for the existence and development of cities, and play a very important role in the urban economy. Currently, the urban infrastructures in China are principally invested and operated by the government, featuring a single channel for investment and financing, inefficient management and operation, and backward investment and financing system for urban infrastructures, which are constraining the country's economic development and social advancement. Therefore, it is of great importance to research the investment and financing system for urban infrastructures under the conditions of market economy.